Unemployment and Gross Domestic Product: Evidence from Papua New Guinea - Cahya Purnama Asri (Profesional Muda Cendekia Publishing, 2021)
The principal link through which economic growth is transmitted to the poor is the amount of employment it generates which derives from the fact that labor is about the only resource in which the poor are relatively abundant, thus, for the poor, the productive use of their plentiful factor, labor, is the principal way to overcome poverty. Many factors affect the gross domestic product, such as unemployment. The objective of this research is to determine the influence of unemployment on the gross domestic product, especially in Papua New Guinea. This research uses quantitative methods and linear regression analysis. The results of the analysis show that there is a significant influence of unemployment on GDP in Papua New Guinea for the period 1991 – 2019. The influence of unemployment on GDP in Papua New Guinea is significant because of the small number of people and most of them are workers, unemployment is very influential on GDP.